2008
DOI: 10.1097/inf.0b013e31817ef4fd
|View full text |Cite
|
Sign up to set email alerts
|

Biennial Spring Activity of Human Metapneumovirus in Austria

Abstract: HMPV activity varies substantially from year to year, both in the frequency and timing of illness and shows a biennial pattern of alternating winter and spring activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 24 publications
16
33
0
Order By: Relevance
“…Our initial observations revealed that only a few nasopharyngeal samples tested positive for hMPV in the first winter season, followed by an epidemic in the next winter season. In the meantime, epidemiological observations in Austria, Germany and Sweden have suggested that hMPV activity appears to follow a biannual cycle [1,25,31] similar to previous findings with respiratory syncytial virus (RSV) in Europe [10,11]. Here, we present the results from our continuous ongoing surveillance and provide further evidence that hMPV causes biannual major epidemics.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our initial observations revealed that only a few nasopharyngeal samples tested positive for hMPV in the first winter season, followed by an epidemic in the next winter season. In the meantime, epidemiological observations in Austria, Germany and Sweden have suggested that hMPV activity appears to follow a biannual cycle [1,25,31] similar to previous findings with respiratory syncytial virus (RSV) in Europe [10,11]. Here, we present the results from our continuous ongoing surveillance and provide further evidence that hMPV causes biannual major epidemics.…”
Section: Introductionsupporting
confidence: 68%
“…Continued surveillance now supports the assumption of a biannual pattern and in the meantime three other groups came to the same conclusion [1,25,31]. In a retrospective RT-PCR-based study from Sweden, hMPV was found in 143 of 4,989 specimens from patients of all ages with respiratory tract infection [25].…”
Section: Discussionmentioning
confidence: 84%
“…15 We also observed a biennial pattern for HMPV of alternating early and late season from 2008 to 2014, which was not seen for RSV or influenza. 16,17 The most prevalent HMPV diagnostic method reported shifted from antigen detection to PCR during 2008 to 2014. The shift toward increased reporting of PCR tests likely reflects changes in conventional diagnostic testing among participating NREVSS laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…HMPV infections can occur throughout the year, but seasonality has been described in several studies, with the epidemiological peak occurring 1 to 2 months later than that observed for RSV epidemics (2,3,107,157,193,245). The intriguing question of whether different HMPV lineages are associated with differences in clinical courses of disease has so far remained unresolved.…”
Section: Clinical Epidemiologymentioning
confidence: 99%
“…Reinfection with HMPV occurs, although repeated infections are more likely to be limited to the upper respiratory tract in otherwise healthy children (248,253). Some data suggest that dominant HMPV strains vary by season, presumably to avoid herd immunity, and thus reinfection may be more likely with heterologous viruses (2,3). Further studies are needed to clarify the importance of antigenic variation of HMPV in human populations with respect to the clinical course of infection.…”
Section: Symptoms and Pathologymentioning
confidence: 99%